The Usborne Official Astronaut's Handbook (Handbooks) - Louie Stowell (London Usborne Publishing Ltd., 2015)
Discover how you become an astronaut, the training you must undertake, how you travel into space and what you do when you're up there. With a foreword from ESA astronaut Tim Peake, the first British astronaut to embark on a mission to the International Space Station. Published in association with the UK Space Agency.